2017
DOI: 10.3390/f8100375
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Pine Monocultures and Mixed Pine-Hardwood Stands on Reclaimed Surface Mined Land in Eastern Kentucky: Implications for Forest Resilience in a Changing Climate

Abstract: Surface mining and mine reclamation practices have caused significant forest loss and forest fragmentation in Appalachia. Shortleaf pine (Pinus echinata) is threatened by a variety of stresses, including diseases, pests, poor management, altered fire regimes, and climate change, and the species is the subject of a widescale restoration effort. Surface mines may present opportunity for shortleaf pine restoration; however, the survival and growth of shortleaf pine on these harsh sites has not been critically eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
5
9
0
Order By: Relevance
“…Black locust typically sustains moderate to high survival (53-100%) on mined sites in the first three to five years after planting [28,39], attributing to its favorability for mine reforestation. White oak survival in this study (68.2-80.5%) was also similar to that found by Emerson et al (2009) [39] when planted within weathered gray and unweathered brown sandstone mine spoils (70-80%) and by Bell et al (2017) [40] when planted in a mixed pine-hardwoods polyculture (50-80%). Shortleaf pine survivals observed in this study were at the lower extent of shortleaf pine survivals found by Bell et al (2017; 29-58%) [40].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Black locust typically sustains moderate to high survival (53-100%) on mined sites in the first three to five years after planting [28,39], attributing to its favorability for mine reforestation. White oak survival in this study (68.2-80.5%) was also similar to that found by Emerson et al (2009) [39] when planted within weathered gray and unweathered brown sandstone mine spoils (70-80%) and by Bell et al (2017) [40] when planted in a mixed pine-hardwoods polyculture (50-80%). Shortleaf pine survivals observed in this study were at the lower extent of shortleaf pine survivals found by Bell et al (2017; 29-58%) [40].…”
Section: Discussionsupporting
confidence: 84%
“…Mean tree heights three years post-planting reported by Showalter et al (2007) [55] in response to spoil type in Virginia appear to indicate growth rates similar to those in this study. Mean shortleaf pine heights reported by Bell et al (2017;10.5 cm) [40] were comparable to mean heights in this study. Similar first-year growth rates for shortleaf pine were also found by Kabrick et al (2015) [56] for underplanted pines in the Missouri Ozark Highlands, indicating that shortleaf pine growth on reclaimed surface mines may approximate that of one-year-old pines regenerating under a closed-canopy forest.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this issue, the first-year results from two experiments conducted in the reclaimed Appalachian surface mines are presented. Bell et al [17] compared the survival and growth of native shortleaf pine to those of non-native loblolly pine (Pinus taeda). Hackworth et al [18] studied herbivore damage in different tree species and how it could be reduced.…”
Section: New and Existing Challenges Along The Seedling Production Chainmentioning
confidence: 99%